(untitled) (Journal of Universal Science Research, 2023)
Modern technology has revolutionized the teaching and learning of chemistry, providing a platform for students to experience hands-on learning, interactive simulations, and digital resources. This essay explores the role of modern technology in teaching chemistry and its impact on student learning outcomes. It highlights the benefits of technology integration in the chemistry classroom and addresses potential concerns associated with its use. Additionally, this essay includes annotated references, tables, pictures, and diagrams to provide a comprehensive overview of the topic.